Bi-reforming of methane with steam and CO2 under pressurized conditions on a durable Ir–Ni/MgAl2O4 catalyst. Issue 88 (16th October 2020) - Liu, Zhongxian; Gao, Feifan; Zhu, Yi-An; Liu, Zhicheng; Zhu, Kake; Zhou, Xinggui
Abstract : Ir–Ni/MgAl2 O4 is found to be a durable catalyst for methane reforming with steam and carbon dioxide under high pressure conditions. Abstract : High pressure reforming of methane is critical for process economics, but imposes increased risk of catalyst coke deposition. Herein, a coke- and sintering-resistant Ir–Ni alloy catalyst is presented, which is durable in methane bi-reforming at 850 °C and 20 bars for up to 434 h.